Equivalence and Standard Scores of the Hurlbert Index of Sexual Assertiveness Across Spanish Men and Women - Santos-Iglesias, Pablo; Vallejo-Medina, Pablo; Sierra, Juan C. (Anales de Psicología / Annals of Psychology, 2013)
The purpose of the present study was to analyze the measurement invariance and differential item functioning of the Spanish version of the Hurlbert Index of Sexual Assertiveness across gender. The sample was composed of 1,600 women and 1,598 men from Spain, with ages ranging from 18 to 84 years old. The Hurlbert Index of Sexual Assertiveness showed partial strong invariance for men and women, as items 2, 9, and 13 had different intercept values between groups. The differential item functioning analysis showed that only item 2 (“I feel that I am shy when it comes to sex”) flagged moderate uniform differential item functioning. More specifically, women tended to respond “Always” to this item more frequently than did men. Results strongly suggested eliminating those three items (2, 9, and 13), resulting in a final version with 16 items clustered into two dimensions. Standard scores for both Initiation and No Shyness/Refusal reflected traditional sexual scripts for men and women.